The struggle between china and india in the brics bloc by a new global leadership - Pacheco Pedroza, Volmar Andrés (Universidad Francisco de Paula Santander, 2016)
The configuration of a new international order has forged alliances, multilateralism or cooperative activities aimed at the development of agreements or pacts which result in the improvement of international relations and strategies, but there are many countries that use these partnerships as platforms to impose or develop a strong foreign policy that represents a new scheme within the international order because these countries want to be leaders in economic, military and political aspects, allowing through hard power as hegemony.China and India have become in recent years on two poles of power, to try to get the best advantage to acquire global leadership that locate them in scenarios of power with greater etermination and a new role in the international context through one of the many organizations of multilateralism in which they are immersed. However, between the two has set a competition where through tools and similar initiatives are intended to conquer the international commercial and financial market to reach those other scenarios of power.